(untitled) (World Economics and Finance Bulletin, 2024)
The study aims to assess the impact of hedging accounting practices on credit and liquidity issues. Its goal is to pinpoint the crucial practices that reduce the financial risks that economic units confront, especially in situations where the future is unpredictable and financial hazards originate from the financing aspect of operations—particularly when debt dependence rises. Risk is associated with quantified probability of loss or inability to attain value, in contrast to uncertainty, which is an immeasurable concept. Additionally, a sample of commercial banks listed on the Iraq Stock Exchange will be subjected to hedging accounting methods as part of the study, and their efficacy in reducing financial risks in the face of rapidly changing banking institutions and shifting environmental conditions will be evaluated. The study aims to assess the impact of hedging accounting practices on credit and liquidity issues. Its goal is to pinpoint the crucial practices that reduce the financial risks that economic units confront, especially in situations where the future is unpredictable and financial hazards originate from the financing aspect of operations—particularly when debt dependence rises. Risk is associated with quantified probability of loss or inability to attain value, in contrast to uncertainty, which is an immeasurable concept. Additionally, a sample of commercial banks listed on the Iraq Stock Exchange will be subjected to hedging accounting methods as part of the study, and their efficacy in reducing financial risks in the face of rapidly changing banking institutions and shifting environmental conditions will be evaluated.